DETERMINATION OF EMOTIONAL INTELLIGENCE, INTELLECTUAL INTELLIGENCE, AND SPIRITUAL INTELLIGENCE ON EMPLOYEE PERFORMANCE THROUGH PROFESSIONALISM IN THE AIRPORT BUSINESS AGENCY HANG NADIM, BATAM CITY - Sitorusa, Sardin; Wibisono, Chablullah; Indrayani,; Nurhatisyah, (International Journal of Psychosocial Rehabilitation, 2020)
There are employee performance problems that are determined by emotional intelligence, intellectual intelligence, and spiritual intelligence through professionalism as intervening in the Batam City Hang Nadim Airport Business Entity. Respondents in this study were employees who worked at the Hang Nadim Airport Business Agency in Batam City, totaling 120 people. Validity and reliability were tested using SPSS version 20.0, then the analysis of independent variables, mediator variables and dependent variables using the SEM test using AMOS version 24.0. From the results of the study note that there is a direct influence of emotional intelligence on professionalism, there is no direct influence of intellectual intelligence on professionalism, there is a direct influence of spiritual intelligence on professionalism, there is no direct effect of emotional intelligence on employee performance, there is no direct influence of intellectual intelligence on employee performance, there is no direct influence of spiritual intelligence on employee performance, engraved the direct influence of professionalism on employee performance. Changes in Professionalism are influenced by Emotional Intelligence, Intellectual Intelligence and Spiritual Intelligence by 72.7%, while changes in Employee Performance are influenced by Emotional Intelligence, Intellectual Intelligence and Spiritual Intelligence by 75.5%. With this research the hypotheses of emotional intelligence, intellectual intelligence, and spiritual intelligence on performance through professionalism are answered.